Sampling of beach sand in Kerteh, Terengganu / Md. Fauzi Ahmad, Nurul Azma Zakaria and Mohmad Razip Selamat - Ahmad, Md. Fauzi; Zakaria, Nurul Azma; Selamat, Mohmad Razip (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
In soil investigation activity, it is normal that focus is made on sampling of undisturbed soft cohesive soils. Tri-axial test and consolidation test are the two key tests to be performed on these samples. At other sampling locations within a boring point, undisturbed sampling and SPT counts are sufficient. However in sandy areas, sampling is normally not carried out due to difficulty of holding the sample within the sampling tube during removal from the borehole. This paper related the experience in sampling of Kerteh Beach Sand in Kerteh, Terengganu. Kerteh which used to be a small town has now become the center of petrochemical industries in Malaysia. Major infrastructure work such as PETRONAS Gas Processing Plant, Kuantan-Kerteh Railway had been completed in the area. A special sampling tube was manufactured to sample the sand. The sampling was successful and assisted in understanding soil behaviour in the area when subjected to engineering activities.